Parents' satisfaction with the teledentistry method during the COVID-19 pandemic: A study in Java and Bali - Sujatmoko, Prisninda Prilyan Geraldine; Laksmiastuti, Sri Ratna (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: The coronavirus (COVID-19) pandemic situation in Indonesia has caused increased anxiety, especially among parents trying to provide health services for their children. The concerns are about cross-contamination through aerosol splashes and contamination by the virus on instruments and in dental offices. Therefore, the government urges the public to use telemedicine. Telemedicine is a digital-based remote health service. The service utilizes information and communication technology. Purpose: This study aims to assess the satisfaction of parents of pediatric dental patients in using teledentistry during the COVID-19 pandemic. Methods: An analytic observational study with a cross-sectional approach was arranged. Data was gathered through questionnaires distributed to parents who live in Java and Bali using the Google Forms platform, consisting of 15 questions with 6 domains of questions. Results: The results showed that 201 respondents were parents of pediatric dental patients, including 123 female respondents and 78 male respondents. The average age of respondents is dominated by the age group 36–40, which included 68 respondents. Two hundred and one respondents were satisfied with dental health services using teledentistry. Conclusion: Parents of pediatric dental patients are generally satisfied with the quality of dental and oral health services using the teledentistry method.